Sifat Fisik, Amilograf, dan Morfologi Pati Biji Lai (Durio kutejensis) Asetilasi Menggunakan Asetat Anhidrat - Siti Masithah Fiqtinovri; Ashri Mukti Benita; Djagal Wiseso Marseno; Yudi Pranoto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Lai (Durio kutejensis) seed starches have a high retrogradation ability and low paste stability so that its function in food industry is less widespread. This phenomenon can be overcome by starches modification, such as acetylation using asetat anhidrat as modifying agent. This study aims to observe the physical properties of acetate starch such as swelling power and solubility, morphological characteristics, and amylographic properties (retrograde rate, viscosity, gelatinization temperature) and the results will be compared to native starch. Lai seed starches was acetylated using asetat anhidrat 3% and 4%, the reaction time variation was 15, 30, 45 and 60 minutes and the reaction pH used ranged from 8-8.5. Acetylation with a different amount of asetat anhidrat (3% and 4%) and different time of reaction (15, 30, 45, 60 min) give an optimum result of DS in 4% of asetat anhidrat with 15 minute of reaction time. DS that reached at those condition is 0.22 and has the same tipe as native starch (tipe A). The result of FTIR shown that there’s a new peak at 1735 cm-1 was a part of carbonyl group and the weakening of hydroxyl group peak of acetate starch. Acetylation decreased the final viscosity from 1472 cP to 1170 cP, setback value from 172 cM to 31cP, and breakdown from 798 cP to 350 cP. Meanwhile, the pasting temperature increased after acetylation from 71.82 °C to 76.05 °C. These result indicate that acetylation increased the resistance of retrogradation, and high pasting stability.